Studi Literatur: Dampak Media Pembelajaran Berbasis Android Terhadap Hasil Belajar Informatika Siswa Menengah Atas - Salma Fitria Shohifah; Iman Nasrulloh; Aceng Ahmad Rodian Susila (Jurnal Media Computer Science, 2026)
This study aims to comprehensively analyze the impact of Android-based learning media on students’ Informatics learning outcomes in Senior High Schools. The research was conducted using a literature study approach by reviewing 30 scientific articles published between 2020 and 2025 from accredited national and international journals. The analysis focused on aspects of media design, curriculum integration, learning effectiveness, and improvements in students’ cognitive and affective learning outcomes. The review results show that Android-based learning media significantly enhance learning engagement, motivation, and students’ performance compared to conventional teaching methods. Most studies reported an average increase in learning outcomes ranging from 15% to 35% after the implementation of Android-based learning media. However, several limitations were identified, such as dependency on digital infrastructure and the lack of teacher training in interactive content development. Based on these findings, it can be concluded that Android-based learning media have great potential to improve Informatics learning outcomes in high schools, provided that their use is supported by institutional policies, teachers’ digital literacy, and contextual instructional design. This study also provides recommendations for future research to explore the integration of artificial intelligence and gamification in Android-based learning media.